Analisis Bibliometrik Publikasi Isu Kebocoran Data Menggunakan VOSviewer - Hanissa Rizki Kurnia; Aisyah Zahrah; Elvia Ichsazene Dina Adha; Nur Aini Rakhmawati (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
Data leakage can harm individuals who experience it, such as identity theft, financial fraud, or even physical security threats. This study aims to analyze scientific publications and research activities in data leakage using bibliometric techniques by involving quantitative analysis using a set of journals as reference sources. The literature for this study was obtained using Publish or Perish software with the keyword "data leakage" and a search result limit of 500. Furthermore, from these results, 85 journals relevant to the research topic were selected for visualization using VOSviewer software. The results showed that the highest number of data leakage publications occurred in 2021, namely 30 journals published that year. Based on the results of the bibliometric analysis conducted, it is known that there are 9 clusters based on keywords and 19 clusters based on author. The most frequently researched keywords include personal data, privacy, data leakage, legal protection, security, cryptography, encryption, and description. On the other hand, some keywords are rarely discussed in publications, namely, air transportation, electronics, and Caesar.